CUTE: A Cryogenic Underground TEst facility at SNOLAB - Camus, Philippe; Corbett, Jonathan; Crawford, Sean; Dering, Koby; Fascione, Eleanor; Gerbier, Gilles; Germond, Richard; Ghaith, Muad; Hall, Jeter; Hong, Ziqing; Kubik, Andrew; Mayer, Adam; et al. (Frontiers in Physics, 2024)
Low-temperature cryogenics open the door for a range of interesting technologies based on features like superconductivity and superfluidity, low-temperature phase transitions or the low heat capacity of non-metals in the milli-Kelvin range. Devices based on these technologies are often sensitive to small energy depositions as can be caused by environmental radiation. The Cryogenic Underground TEst facility (CUTE) at SNOLAB is a platform for testing and operating cryogenic devices in an environment with low levels of background. The large experimental chamber (O(10) L) reaches a base temperature of ∼ 12 mK; it can hold a payload of up to ∼ 20 kg and provides a radiogenic background event rate as low as a few events/kg/keV/day in the energy range below about 100 keV, as well as a negligible muon rate (O(1)/month). CUTE was designed and built in the context of the Super Cryogenic Dark Matter Search experiment (SuperCDMS) that uses cryogenic detectors to search for interactions of dark matter particles with ordinary matter. The facility has been used to test SuperCDMS detectors since its commissioning in 2019. In 2021, it was handed over to SNOLAB to become a SNOLAB user facility after the completion of the testing of detectors for SuperCDMS. The facility will be available for projects 1 Camus et al.that benefit from these special conditions, based on proposals assessed for their scientific and technological merits. This article describes the main design features and operating parameters of CUTE.